2019
DOI: 10.1039/c9cc05122h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Transformer unifies reaction prediction and retrosynthesis across pharma chemical space

Abstract: We develop a machine learning model that tackles both reaction prediction and retrosynthesis by learning from the same dataset. The model is generalizable across chemical space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 20 publications
2
100
0
Order By: Relevance
“…Schwaller et al [22] recently proposed to ignore reactant and reagent roles for the reaction prediction task. In contrast to previous works [32,33,35,36], the single-step retrosynthetic model presented here predicts reactants and reagents. In an effort to simplify the prediction task, the most common precursors with a length of more than 50 tokens were replaced by molecule tokens.…”
Section: Molecule Representationmentioning
confidence: 58%
“…Schwaller et al [22] recently proposed to ignore reactant and reagent roles for the reaction prediction task. In contrast to previous works [32,33,35,36], the single-step retrosynthetic model presented here predicts reactants and reagents. In an effort to simplify the prediction task, the most common precursors with a length of more than 50 tokens were replaced by molecule tokens.…”
Section: Molecule Representationmentioning
confidence: 58%
“…An expected feature of machine-learning methods for predictive chemistry is that retraining models on proprietary data ought to allow companies to achieve better predictive ability on chemistries that are used in-house. 58 These in-house chemistries may not be well represented in public or published data sets, which most of the CASP systems are trained on. Researchers from AstraZeneca and the University of Bern applied a workflow for retrosynthetic template extraction 28 and training/application 29 to several public and proprietary data sets and compared the performance of the different models.…”
Section: Section 2: How Is Casp Currently Used In the Pharmaceutical mentioning
confidence: 99%
“…Schwaller and Lee's group successfully applied a Molecular Transformer model to uncertainty-calibrated chemical reaction prediction [9]. Lee also used the Transformer model to unify reaction prediction and retrosynthesis across pharma chemical space [10]. Experiments by the authors on two machine translation tasks showed that the Transformer was superior to the seq2seq model [5].…”
Section: Introductionmentioning
confidence: 99%